Identification of Research Priorities in the Field of Health; Necessity and Feasibility of Implementation - Arash Rashidian; Efat Mohamadi; Taraneh Yousefinezhadi; Elham Dadgar; Sedigheh Salavati; Zahra Beigom Seyed Aghamiri (Tehran University of Medical Sciences, 2019)
Background and Aim: The starting point for any research is the problem-solving and Research Needs Assessment is needed to identify the underlying issues. This study was conducted to determine the research priorities of the Deputy of Health of Tehran University of Medical Sciences. Materials and Methods: The present study was an applied study that was designed and implemented in five stages; 1. holding a workshop to teach nominal group technique; 2. Carrying out interviews and the primary extraction of research priorities; 3. Conducting the first round of nominating sessions; 4. holding the second round of nominal group meetings, 5. Finalizing research prioritization titles. Data were analyzed by Excel and Spss version 19 software. Result: This study was conducted with the participation of 38 people. At first, 1039 minutes of interview, 258 original research titles were extracted. Initial research titles were scored during the 4 sessions. At the end, 75% of the participants rated the 21 study points as 7-9, which were considered as research priorities. The titles "Investigating the root causes of maternal death" was the most priority and "the assessment of the effectiveness of the screening of hypothyroidism" was the least priority. Conclusion: According to findings, there is consensus among stakeholders on research priorities that require investment in generating knowledge related to health goals. Managing the research resources of the organization towards implementing these priorities will lead to a rational allocation of resources for the production of knowledge and applied products, and ultimately to improve the health of the population.